2016
DOI: 10.1371/journal.pone.0159401
|View full text |Cite
|
Sign up to set email alerts
|

Isolating Sperm from Cell Mixtures Using Magnetic Beads Coupled with an Anti-PH-20 Antibody for Forensic DNA Analysis

Abstract: Vaginal swabs taken in rape cases usually contain epithelial cells from the victim and sperm from the assailant and forensic DNA analysis requires separation of sperm from these cell mixtures. PH-20, which is a glycosylphosphatidylinositol-anchored hyaluronidase located on the head of sperm, has important functions in fertilization. Here we describe a newly developed method for sperm isolation using anti-PH-20 antibody-coupled immunomagnetic beads (anti-PH-20 IMBs). Optical microscopy and scanning electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Here, we present a next‐generation differential extraction technology that is, to the best of our knowledge, the most rapid, reliable, accurate, user‐friendly method available. Although there are previously antibody‐based capture approaches proposed for forensic samples, they suffer from loss of efficiency and specificity over time since proteins on the sperm membrane aged over a long‐term storage, as well as during drying process 15, 20, 21. As we have shown in this study, SLeX has multiple binding sites on the sperm surface, making it a unique element for aged forensic sperm samples, allowing our methods to achieve ≈5‐fold higher sperm capture efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we present a next‐generation differential extraction technology that is, to the best of our knowledge, the most rapid, reliable, accurate, user‐friendly method available. Although there are previously antibody‐based capture approaches proposed for forensic samples, they suffer from loss of efficiency and specificity over time since proteins on the sperm membrane aged over a long‐term storage, as well as during drying process 15, 20, 21. As we have shown in this study, SLeX has multiple binding sites on the sperm surface, making it a unique element for aged forensic sperm samples, allowing our methods to achieve ≈5‐fold higher sperm capture efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been reported that this cell separation process results in losses of 60–90% of the male DNA 10, 11, 12, 13. Although there have been multiple attempts for alternative methods to differentially extract sperm using acoustic trapping,14 antibody‐based capture,15 laser microdissection,16, 17, 18 nuclease‐based approaches,19 and magnetic bead‐based separation,20, 21 these methods have not been broadly available in practical applications due to the complexity and low separation yield for sperm. As a result, they are not widely in use in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Another completely different approach to avoid the loss of spermbot velocity would be the guidance with magnetic beads attached to the sperm cell instead of the microtube. The attachment of magnetic beads to the sperm head via sperm‐specific antibodies has been applied successfully for sperm cell separation, e.g., in forensics . However, this requires biochemical functionalization of the sperm membrane, which could interfere with other biological activities of the cell, for instance, the acrosome reaction, which takes place on the surface of the sperm head.…”
Section: Challenges Of Current Approachesmentioning
confidence: 99%
“…Molecular autopsy methods such as lasercapture microdissection (LCM) [94][95][96][97], flow cytometry, fluorescence (FACS) or magnetic (MACS) activated cell sorting methodologies [98][99][100][101] or alternatives [102][103][104] are fields where ongoing research is ensuring the potential to enhance the generation of single source genetic profiles of desired target DNA from cellular mixtures obtained by the initial collection device. Recent advances may provide a successful method for the separation of cellular mixtures of small numbers of cells [105], but complete separation of different cells with same morphology and gender origin seems to be a challenge that is still to be adequately addressed [98,102].…”
Section: Collection Devices and Paraffin Embedded Tissuesmentioning
confidence: 99%